Relationships between anthropometric traits, body composition and aerobic capacity in male soccer players aged 13-15 years - Boraczynski, M.; Boraczynski, T.; Podstawski, R.; Wójcik, Z. (Journal of Kinesiology and Exercise Sciences, 2015)
Purpose. This study describes the relationships between body dimensions, body composition and aerobic capacity in young soccer players at a targeted stage of their sports training. Basic procedures. A group of 27 soccer players (13.6-15.6 years of age) was examined during a 2-year training period. Anthropometry, body composition and aerobic capacity were assessed. Main findings. Positive correlations were found between body mass (BM), fat free mass (FFM), skeletal muscle mass (SMM), and absolute maximal oxygen uptake (VO2max) and physical working capacity (PWC170) values (p < 0.05). By contrast, there were unexpected negative correlations between BM, FFM, SMM, and relative VO2max values (p < 0.01). Additionally, negative correlations between BMI and relative VO2max values (p < 0.05) were noted. Conclusions. The negative relationships between BM, FFM, SMM and relative VO2max demonstrated the ineffectiveness of the soccer training process in terms of players` aerobic capacity development. At the same time, decreasing relative aerobic capacity indices in consecutive years clearly point to the inadequate implementation of the training program or misconceptions in shaping aerobic capacity. Therefore, it is necessary to verify the implementation of this program in order to improve players` aerobic capacity.